Geologia, petrografia e geoquímica das rochas plutônicas precambrianas (unidade metadiorítica Ibitutinga e unidade metatrondhjemítica Caburu) intrusivas nas rochas do greenstone Belt Barbacena, São João del Rei, Minas Gerais - Ávila, Ciro Alexandre (1992)
In the southeastern portion of the São Francisco Craton, located between São João Del Rey and Ritápolis cities (Minas Gerai, State) an area of nearly 180 km² of rocks of the Barbacena Greenstone Belt (metaultramafic and amphibolitic rocks, and schists) and associated mafic to felsic plutonic intrusives was mapped. The Granodioritic – Granitic Unit comprises granites, quartz monnzodiorJtes and granodiorites, previously vaguely described in the litera.ture as granite. The parental magmas for this rock unit are interpretated as the most. Possible source of the K-rich solutions responsible for the metasomatic transtormations of the rocks of Ibitutinga Metadioritic Unit and the Caburu Metatrondhjemitic Unil.